The case study of emergency response plan (ERP) implementation during the Malaysia Airlines (MAS) flight MH370 disappearance / Ahmad Nabil Saroni, Muhammad Asraf Abd Samad and Jamaludin Ibrahim - Saroni, Ahmad Nabil; Abd Samad, Muhammad Asraf; Ibrahim, Jamaludin (Penerbit UiTM, 2019)
The unsolved mystery on the disappearance of Malaysia Airlines (MAS) Flight MH370 has been one of the most highly discussed air crashed incidents in recent times. The doomed flight was en route from Kuala Lumpur to Beijing with a total of 239 people on board. Even after years of investigation and searching efforts that ended recently, investigators have not been able to identify the reason that led to the deviation from its original route shortly after taking off. Accordingly, this case study evaluates the implementation of Malaysia Airlines' Emergency Response Plan (ERP) in handling the incident, particularly in the early crucial weeks. The data were collected from the ERP practices retrieved from several articles, reports, and journals; and they were analyzed by using a qualitative case study methodology. This study hypothesizes that there were a number of loopholes that led to an ineffective implementation of Malaysia Airlines (MAS)' ERP steered by the Emergency Response Team (ERT) and Malaysian authorities; that was further worsened by both internal and external crisis elements ranging from unverified information to the shortcomings in the Search and Rescue (SAR) operation conducted.